MEMBANGUN BADAN USAHA MILIK SEKOLAH DI SD MUHAMMADIYAH DENPASAR - Wakhudin Wakhudin; Dedy Irawan; Try Yuliansyah Bintaro (Yayasan Education and Social Center, 2023)
This community service report aims to socialize the need for School-Owned Enterprises (BUMS) as an alternative source of funding for education units. Each school does have the opportunity to get funding from the government and local government, as well as the community, but in reality the education unit operates the education budget roughly. Therefore, education units need to find alternative sources of education funding. One way is to establish a School-Owned Enterprise. This BUMS is the same position as State-Owned Enterprises (SOEs) in the central government, Regional Owned Enterprises (BUMD) for provincial, district and city governments, and Village-Owned Enterprises (BumDes). The recommended BUMS can be PT, CV or Cooperative. But among the three economic institutions, cooperative is the most suitable for schools. Because, in cooperatives it is not only an economic matter, but in it there is a spirit of mutual assistance, and the spirit of education. BUMS is a manifestation of the creativity of education units under the responsibility of school principals, in addition to educational issues. All BUMS activities are the full responsibility of the principal. However, BUMS is carried out according to the rhythm of the business world, so that this institution is purely a professional economic institution